A Geographic Information System Mobile Application for Road Traffic Crash Data Collection, Management and Analysis - Jude Ubaka Odinfono; Manuel Ndebele; Adekunle Oluseyi Afolabi; Moses Olaniran Olawole (Journal of Geospatial Science and Technology, 2026)
The study addressed the issue of road traffic crashes in developing countries like Nigeria by developing a mobile app called Geographic Information System-Road Traffic Crash Data (GIS-RTCD). The app developed and tested in Southwest Nigeria is designed to transform the collection and management of real-time road traffic crash data by replacing the traditional paper-based method known for its imprecise, missing, contradictory, and disparate data. The app, accessible on Android and iPhone platforms, uses an Epicollect5-implemented mobile user interface, web server, PostgreSQL-based database, Apache Tomcat/Geoserver application/GIS server, and OpenLayers-implemented web service for map data visualization. The app provides precise crash location determination through GPS/geospatial mapping, digitally structures data collection, prevents data duplication, and eliminates labour-intensive tasks associated with manual data processing. The study recommends replacing manual crash data recording systems in Nigeria with the GIS-RTCD app to standardize crash data records and enhance comprehensive data collection for national analysis and research.